The paraglacial adjustment of an Alpine lateral moraine, Bas Glacier d'Arolla, Switzerland - Tonkin, Toby N. (Physical geography, 2023)
Within Alpine catchments, glacial landforms are subject to post-depositional reworking during and following deglaciation. Ice-marginal moraines are thought to rapidly stabilise within ~200 years in this topographic context, although ice-proximal slopes are particularly prone to alteration by debris flows and solifluction. This study investigates landform transformation, documenting geomorphological change at the Bas Glacier d'Arolla, Switzerland. Gully development on a moraine slope was assessed using archive image sets obtained in 1977, 1988 and 2009 to derive historical elevation models. Raster differencing suggests that the mean rate of surface lowering on the upper moraine slope was 7.15 ± 1.83 m (± minimum level of detection) over the observation period (1977-2009), a rate of 0.22 m yr −1 . The erosion of the landform resulted in an incontiguous moraine crestline. Whilst some landforms may undergo limited transformation upon deglaciation, selected sites are subject to rapid geomorphologic change, involving crestline retreat via the initial dissection by gullies, followed by the removal of inter-gully slopes.